Scientific and Methodological Foundations of Primary Education Methodology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The effectiveness of education in primary grades depends on compliance with the principles of education and the correct selection of educational methods and techniques, as well as their correct application in practice. Method (Greek) – means “method” and is a set of methods for performing a specific task, practical or theoretical mastery (knowledge) of existence, serving to achieve a specific goal. The pedagogical meaning of the concept of method is to equip with knowledge, skills, and qualifications and apply them in practice.